Exhaustive TORCH pathogen diagnostics corroborate zika virus etiology of congenital malformations in Northeastern Brazil - Moreira-Soto, Andres; Jänisch, Thomas (mSphere, 2018)
The Latin American 2015-2016 Zika virus (ZIKV) outbreak was associated with an increase in microcephaly predominantly in northeastern Brazil. To comparatively investigate infectious causes of congenital malformations, we performed a nested case-control study in 32 mothers of cases of suspected congenital Zika syndrome (CZS) and 160 age-matched controls from Bahia, northeastern Brazil. We collected clinical and imaging data and assessed past exposure to ZIKV, Chikungunya virus (CHIKV), dengue virus, and 8 established TORCH (Toxoplasma gondii, Treponema pallidum, rubella virus, cytomegalovirus, herpes simplex virus 1 [HSV-1] and HSV-2, varicella-zoster virus, parvovirus B19) pathogens using multiple serological tests. Heterogeneous symptoms prevented unequivocal diagnosis of CZS on clinical grounds. Only ZIKV and CHIKV seroprevalence rates differed significantly between cases and controls (93.8% versus 67.8% for ZIKV [Fisher’s exact text, P = 0.002] and 20.7% versus 8.2% for CHIKV [χ2, P = 0.039]). High ZIKV seroprevalence rates in cases could not be explained by previous dengue virus infections potentially eliciting cross-reactive antibody responses affecting ZIKV serological tests. In conditional logistic regression analyses, only ZIKV was significantly associated with congenital malformations (P = 0.030; odds ratio, 4.0 [95% confidence interval, 1.1 to 14.1]). Our data support an association between maternal ZIKV exposure and congenital malformations. Parallels between the discrepant ZIKV and CHIKV seroprevalence rates between cases and controls and similar seroprevalence rates between cases and controls for the sexually transmitted T. pallidum and HSV-2 may suggest the occurrence of predominantly vector-borne transmission in our study population. High seroprevalence of TORCH pathogens suggests that exhaustive diagnostics will be necessary in the aftermath of the ZIKV outbreak and provides baseline data for longitudinal studies on ZIKV pathogenesis. - IMPORTANCE The Latin American Zika virus (ZIKV) outbreak had a major impact on reproductive health worldwide. The reasons for the massively increased reports of neonatal microcephaly in northeastern Brazil are still unclear. Beyond the technical limitations of laboratory diagnostics, unambiguous diagnosis of ZIKV as the cause of congenital malformations is hampered by similar clinical pictures elicited by other pathogens known as TORCH pathogens. We performed a case-control study comparing mothers of children with congenital malformations to age-matched controls from Salvador, Brazil, one of the areas most extensively affected by the ZIKV outbreak. The ZIKV and Chikungunya virus seroprevalence rates differed significantly, whereas the levels of maternal exposure to TORCH pathogens were similar between cases and controls. Our data support a link between maternal ZIKV infection and congenital malformations and suggest the occurrence of predominantly vector-borne ZIKV transmission in these cases. In addition, some highly prevalent TORCH pathogens may be misinterpreted as representative of ongoing ZIKV activity in the absence of exhaustive diagnostics in northeastern Brazil.
Gesehen am 10.04.2019